Level of Oral Questions Used by New and Experienced Teachers in Mathematics Teaching in Primary Schools - Mahmud, Muhammad Sofwan (International Journal of Psychosocial Rehabilitation, 2020)
This study was conducted to study the level of oral questions used by new and experienced teachers in the mathematics teaching process. The use of high-level oral questions can help improve students’ thinking and understanding of mathematics teaching. Data from the qualitative case study was collected through observations, semi-structured interviews, document analysis and field notes. Six mathematics teachers from six different primary schools in a district in Malaysia were selected as participants of the study using purposive sampling method. The data were then analyzed using a constant comparative method to identify the patterns and themes that emerged from the data obtained. The study found that new and experienced teachers focused more on low-level oral questioning in the mathematics teaching process. The oral questions posed emphasize the memorization aspects of mathematical procedures and formulas. This indirectly diminishes the opportunity for students to train their thinking to a higher level. The implication of this study is that teachers need to be given more in-depth training to help them improve their skills in implementing oral questioning processes to help improve students’ high-level thinking skills.